SERAT PAMORING KAWULA GUSTI Perwujudan Islam Kejawen - Barowi, Ahmad (Sabda: Jurnal Kajian Kebudayaan, 2008)
Serat Pamoring Kawula-Gusti is a form of elements of Java Islamic mysticism. The book contains points of doctrine of Islamic mysticism or Sufism processed and adapted to the Javanese thoughts. The book is often called suluk when in the form of poetry and called wirid when in the form of prose. The largest and richest book of suluk with elements of Sufism, namely Serat Centhini, while the books of famous wirid Serat Wirid Hidayat Jati and Kitab Kunci Swargo. The books are the books of Java sufism enriched and refined with elements of mysticism and the teachings of nobility. Serat Pamoring Kawula-Gusti is a crowning invaluable achievement of Javanese culture. Javanese culture is progressing brilliantly during its rise since the kingdom of Kartasura. Main ideas taught by R. Ng. Ranggawarsita in the book is an expression of the basics of Islam to the Java language and lifestyle in accordance with the teachings of Islamic mysticism (Sufism). Mystical teaching of Islam expressed in the language and lifestyle of Java is that life in this world is not a destination, but a journey towards a more perfect life to the afterlife or in union with God again.